Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s10461-018-2209-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevention in Rural Appalachian Jails: Implications for Re-entry Risk Reduction Among Women Who Use Drugs

Abstract: Rural women are at risk for health consequences (such as HIV) associated with substance misuse, but targeted interventions are limited for this population. Jails provide an underutilized opportunity for outreach to high-risk women in rural Appalachian communities. Rural women were randomized to either the NIDA Standard education intervention (n = 201) or the NIDA Standard plus motivational interviewing (MI-HIV; n = 199) while in jail. Outcomes focused on HIV risk behaviors 3 months post-release from jail. Decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Specifically, condom demand decreased more rapidly with increased cost for individuals reporting higher AUDIT scores and a recent history of unprotected sexual activity, whereas condom demand decreased less rapidly for participants with greater STI knowledge. Previous research has documented the benefits of educational interventions targeting improved HIV knowledge to decrease risky sexual behaviors and increase intentions to engage in condom‐protected sex, including studies in high‐risk populations (e.g., individuals reporting nonmedical opioid use; Dunn et al, ; Festinger, Dugosh, Kurth, & Metzger, ; Medley, Kennedy, O'Reilly, & Sweat, ; Staton et al, ). The current findings suggest that one mechanism by which improved STI knowledge could enhance sexual health is by reducing sensitivity to the barriers/costs of protected sexual activity (like price).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, condom demand decreased more rapidly with increased cost for individuals reporting higher AUDIT scores and a recent history of unprotected sexual activity, whereas condom demand decreased less rapidly for participants with greater STI knowledge. Previous research has documented the benefits of educational interventions targeting improved HIV knowledge to decrease risky sexual behaviors and increase intentions to engage in condom‐protected sex, including studies in high‐risk populations (e.g., individuals reporting nonmedical opioid use; Dunn et al, ; Festinger, Dugosh, Kurth, & Metzger, ; Medley, Kennedy, O'Reilly, & Sweat, ; Staton et al, ). The current findings suggest that one mechanism by which improved STI knowledge could enhance sexual health is by reducing sensitivity to the barriers/costs of protected sexual activity (like price).…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight studies that were included in the integrative review, five were identified in MEDLINE (25)(26)(27)(28)(29) , one in Cochrane (30) , one in ScienceDirect (31) , and one in CINAHL (32) . Most of the studies were developed in the United States (7) (25)(26)(27)(28)(29)(30)32) and all of them were written in English. Only one article was prepared in Brazil (31) .…”
Section: Resultsmentioning
confidence: 99%
“…A chart was created to summarize the main characteristics of the studies (Figure 3). Staton, et al, 2018 (25) United States…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations